تشخيص المراحل الباكرة من تليُّن غضروف الداغصة وتدبيرها بوساطة المنظار - جوني, أحمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (49) مراهقاً وشاباً: (63) مفصل ركبة. يعانون من ألم في مقدمة الركبة. أكثر من نصف الحالات كانت من الذكور (55.1%). أُكِّدَ تشخيص تليّن غضروف الداغصة في جميع الحالات بالتنظير المفصلي الذي سمح بتحديد مكان الإصابة ودرجتها, كما سمح بإجراء مجموعة من التدابير والإجراءات التنظيرية مثل: الغسيل والإرواء- التثقيب- الحلاقة- خزع القيد الوحشي. كانت نسبة النتائج الممتازة أو الجيدة (93.6%): وهذه النتائج الإيجابية تؤكد الفعالية الكبيرة للتنظير المفصلي بوصفها وسيلة تشخيصية وعلاجية لتليّن غضروف الداغصة ولاسيما في المراحل الباكرة منه. Our study included (49) adolescents and young adults: 63 knees, who suffered from pain on the anterior aspect of the knee. Over half of all Cases were males (55.1%). Diagnosis of Chondromalacia Patellae was confirmed by arthroscopy, which made it possible to define the area of the lesion, and stage of Chondromalacia. Arthroscopy also gave a chance to do a group of arthroscopic managements, like irrigation, drilling, shaving, Lateral retinacular release. Results were excellent or good in (93.6%). These positive results confirm the high effect of arthroscopy as an excellent diagnostic and therapeutic management meansof chondromalacia patella, especially in early stages.